Towards an understanding of the molecular basis of effective RNAi against a global insect pest, the whitefly Bemisia tabaci - Luo, Yuan; Chen, Qingguo; Luan, Junbo; Chung, Seung Ho; Van Eck, Joyce; Turgeon, R.; Douglas, Angela E. (Insect biochemistry and molecular biology, 2017)
In planta RNAi against essential insect genes offers a promising route to control insect crop pests, but is constrained for many insect groups, notably phloem sap-feeding hemipterans, by poor RNAi efficacy. This study conducted on the phloem-feeding whitefly Bemisia tabaci reared on tomato plants investigated the causes of low RNAi efficacy and routes to ameliorate the problem. Experiments using tomato transgenic lines containing ds-GFP (green fluorescent protein) revealed that full-length dsRNA is phloem-mobile, ingested by the insects, and degraded in the insect. We identified B. tabaci homologs of nuclease genes (dsRNases) in other insects that degrade dsRNA, and demonstrated that degradation of ds-GFP in B. tabaci is suppressed by administration of dsRNA against these genes. dsRNA against the nuclease genes was co-administered with dsRNA against two insect genes, an aquaporin AQP1 and sucrase SUC1, that are predicted to protect B. tabaci against osmotic collapse. When dsRNA constructs for AQP1, SUC1, dsRNase1 and dsRNase2 were stacked, insect mortality was significantly elevated to 50% over 6 days on artificial diets. This effect was accompanied by significant reduction in gene expression of the target genes in surviving diet-fed insects. This study offers proof-of-principle that the efficacy of RNAi against insect pests can be enhanced by using dsRNA to suppress the activity of RNAi-suppressing nuclease genes, especially where multiple genes with related physiological function but different molecular function are targeted. [Display omitted] •Tomato plants transformed with dsRNA deliver full-length dsRNA to the phloem-feeding whitefly Bemisia tabaci.•Orally-acquired dsRNA is degraded in the body of the whitefly B. tabaci.•The B. tabaci genome encodes three non-specific nucleases, two of which are expressed in the gut.•RNAi-mediated suppression of nuclease expression reduces degradation of other dsRNA molecules ingested by whiteflies.•Whitefly mortality on diets is enhanced by stacking oral RNAi against insect osmoregulation genes and nucleases.